Mesenchymal Stem/Stromal Cell-Derived Extracellular Vesicles Elicit Better Preservation of the Intra-Renal Microvasculature Than Renal Revascularization in Pigs with Renovascular Disease - Christopher M. Ferguson; Rahele A. Farahani; Xiang-Yang Zhu; Hui Tang; Kyra L. Jordan; Ishran M. Saadiq; Amir Lerman; Lilach O. Lerman; Alfonso Eirin (Cells, 2021)
Background: Percutaneous transluminal renal angioplasty (PTRA) confers clinical and mortality benefits in select ‘high-risk’ patients with renovascular disease (RVD). Intra-renal-delivered extracellular vesicles (EVs) released from mesenchymal stem/stromal cells (MSCs) protect the kidney in experimental RVD, but have not been compared side-by-side to clinically applied interventions, such as PTRA. We hypothesized that MSC-derived EVs can comparably protect the post-stenotic kidney via direct tissue effects. Methods: Five groups of pigs (n = 6 each) were studied after 16 weeks of RVD, RVD treated 4 weeks earlier with either PTRA or MSC-derived EVs, and normal controls. Single-kidney renal blood flow (RBF) and glomerular filtration rate (GFR) were assessed in vivo with multi-detector CT, and renal microvascular architecture (3D micro CT) and injury pathways ex vivo. Results: Despite sustained hypertension, EVs conferred greater improvement of intra-renal microvascular and peritubular capillary density compared to PTRA, associated with attenuation of renal inflammation, oxidative stress, and tubulo-interstitial fibrosis. Nevertheless, stenotic kidney RBF and GFR similarly rose in both PTRA- and EV-treated pigs compared RVD + Sham. mRNA sequencing reveled that EVs were enriched with pro-angiogenic, anti-inflammatory, and antioxidants genes. Conclusion: MSC-derived EVs elicit a better preservation of the stenotic kidney microvasculature and greater attenuation of renal injury and fibrosis compared to PTRA, possibly partly attributed to their cargo of vasculo-protective genes. Yet, both strategies similarly improve renal hemodynamics and function. These observations shed light on diverse mechanisms implicated in improvement of post-stenotic kidney function and position EVs as a promising therapeutic intervention in RVD.